Przestrzenie konfliktów etnicznych w Namibii w powieści kryminalnej "Kamienista ziemia" (2012) Bernharda Baumanna = Spaces of ethnic conflict in Namibia in Bernhard Jaumann`s crime novel "Steinland" (2012) - Rapp, Karolina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Bernhard Jaumann`s suspense-packed crime novel "Steinland" (2012) explores German post-colonial legacy in the context of current land reform policies in Namibia. The most crucial aspect of this paper is the contemplation of the historical heritage of German colonialism, mental, spatial, social and ethnic conflicts, South African occupation, Apartheid and the struggle for freedom until 1990, which shows its effects in the conflicting interests between the long-established farm owners, mostly of German heritage, and the new black elite after 2011 - the time in which the novel takes place.
Keywords: Jaumann, Bernhard (1957- ); powieść kryminalna; literatura niemiecka - tematyka - 21 w.